Model reduction of a flexible-joint robot: a port-Hamiltonian approach - Jardón-Kojakhmetov, Hildeberto; Muñoz-Arias, Mauricio; Scherpen, Jacquelien (IFAC-PapersOnLine, 2016)
In this paper we explore the methodology of model order reduction based on singular perturbations for a flexible-joint robot within the port-Hamiltonian framework. We show that a flexible-joint robot has a port-Hamiltonian representation which is also a singularly perturbed ordinary differential equation. Moreover, the associated reduced slow subsystem corresponds to a port-Hamiltonian model of a rigid-joint robot. To exploit the usefulness of the reduced models, we provide a numerical example where an existing controller for a rigid robot is implemented.
Artículo científico
Keywords: Robots; Metodología; Ecuaciones; Modelos; Research Subject Categories::TECHNOLOGY::Information technology::Computer science::Cognitive science